2018
DOI: 10.3390/ma11122508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CeO2 on Microstructure and Synthesis Mechanism of Al-Ti-C Alloy

Abstract: The effects of CeO2 on the microstructure and synthesis mechanism of Al-Ti-C alloy were investigated by quenching experiment method, while using Al powder, Ti powder, graphite powder, and CeO2 powder as main raw materials. The results showed that the addition of CeO2 was favorable for promoting the formation of TiC particles in Al-Ti-C systems. With CeO2 contents increasing, the distribution of TiC particles were more homogeneous, and the rare earth phase Ti2Al20Ce was formed. CeO2 had little effect on the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[Ce] atoms adsorb on the surface of TiAl 3 , and the reaction (5) forms a core-shell structure of Ti 2 Al 20 Ce coated on TiAl 3 [ 18 ] ( Figure 16 c), which inhibits the growth of TiAl 3 phase crystal nuclei and promotes α-Al nucleation [ 16 , 23 ] ( Figure 16 d). In the meantime, part of the Ti 2 Al 20 Ce phase continuously releases [Ce] atoms [ 17 ] into the melt during the holding process. The [Ce] atoms cluster on the TiC surface ( Figure 16 c) to improve the wettability between TiC and melt Al, preventing the generation of Al 4 C 3 from TiC [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Ce] atoms adsorb on the surface of TiAl 3 , and the reaction (5) forms a core-shell structure of Ti 2 Al 20 Ce coated on TiAl 3 [ 18 ] ( Figure 16 c), which inhibits the growth of TiAl 3 phase crystal nuclei and promotes α-Al nucleation [ 16 , 23 ] ( Figure 16 d). In the meantime, part of the Ti 2 Al 20 Ce phase continuously releases [Ce] atoms [ 17 ] into the melt during the holding process. The [Ce] atoms cluster on the TiC surface ( Figure 16 c) to improve the wettability between TiC and melt Al, preventing the generation of Al 4 C 3 from TiC [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al [ 16 ] investigated the second phases of Al-3Ti-0.2C-1RE grain refiner and found that rare earth elements could be adsorbed onto the surface of TiAl 3 to form a Ti 2 Al 20 RE phase, which hindered the growth of TiAl 3 , the formation of Al 4 C 3 , and the agglomeration of TiC. Ding et al [ 17 ] prepared Al-Ti-C-Ce grain refiners and found that CeO 2 promoted the formation of TiC through the phase analysis of a quenching experiment. Xu et al [ 18 ] confirmed the contribution of the Ti 2 Al 20 Re phases on the anti-fading performance through the refinement experiments of Al-Ti-C-Re grain refiners.…”
Section: Introductionmentioning
confidence: 99%
“…The research of Auffan et al [16] and Liu et al [17] shows that CeO 2 nanoparticles have a high specific surface area, and the smaller the size of CeO 2 nanoparticles, the higher the specific surface area and the greater the activity. Preliminary studies have shown that when the content of CeO 2 was 4 wt.%, it had a significant promoting effect on the Al-Ti-C system [18]. On this basis, it is necessary to further study the effect of CeO 2 particle size on phase transition and microstructure transformation of Al-Ti-C system.…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of rare‐earth oxides on the refiner is currently mainly concentrated on La 2 O 3 and Ce 2 O, and other rare‐earth oxides are less studied. [ 11,12 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of rare-earth oxides on the refiner is currently mainly concentrated on La 2 O 3 and Ce 2 O, and other rare-earth oxides are less studied. [11,12] Therefore, in this article, the Al-TiO 2 -C refiner was prepared by the exothermic dispersion method, and the refining effect was improved by adding Er 2 O 3 powder. The effect of Er 2 O 3 content on the structure of Al-TiO 2 -C refining agent and the refining effect of Al-TiO 2 -C-Er 2 O 3 refining agent on Al-5Cu alloy were studied.…”
Section: Introductionmentioning
confidence: 99%